Novel SBF2 mutations and clinical spectrum of Charcot‐Marie‐Tooth neuropathy type 4B2. Issue 5 (14th August 2018) - Laššuthová, P.; Vill, K.; Erdem‐Ozdamar, S.; Schröder, J.M.; Topaloglu, H.; Horvath, R.; Müller‐Felber, W.; Bansagi, B.; Schlotter‐Weigel, B.; Gläser, D.; Neupauerová, J.; Sedláčková, L.; et al.
Abstract : Biallelic SBF2 mutations cause Charcot‐Marie‐Tooth disease type 4B2 (CMT4B2), a sensorimotor neuropathy with autosomal recessive inheritance and association with glaucoma. Since the discovery of the gene mutation, only few additional patients have been reported. We identified seven CMT4B2 families with nine different SBF2 mutations. Revisiting genetic and clinical data from our cohort and the literature, SBF2 variants were private mutations, including exon‐deletion and de novo variants. The neuropathy typically started in the first decade after normal early motor development, was predominantly motor and had a rather moderate course. Electrophysiology and nerve biopsies indicated demyelination and excess myelin outfoldings constituted a characteristic feature. While neuropathy was >90% penetrant at age 10 years, glaucoma was absent in 40% of cases but sometimes developed with age. Consequently, SBF2 mutation analysis should not be restricted to individuals with coincident neuropathy and glaucoma, and CMT4B2 patients without glaucoma should be followed for increased intraocular pressure. The presence of exon‐deletion and de novo mutations demands comprehensive mutation scanning and family studies to ensure appropriate diagnostic approaches and genetic counseling. Abstract :